MANAJEMEN PENGELOLAAN WAHANA REKREASI OLAHRAGA DI WISATA WATER BLASTER SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to determine the process and the management of existing resources in the recreational vehicle Blaster Water sports in Semarang . This study is a qualitative research methodology . Collecting data using observation , questionnaires , interviews , documents and documentation . The data analysis technique used is descriptive percentage ( DP ) and the method of triangulation . The results of a descriptive study using a percentage , obtained planning process including criteria results 75 % higher , organizing the results obtained 76.3 % including high criteria , the results obtained leadership criteria included a low 53.8 % , controls 83.8 % obtained results are included in the very high criteria . Human resources results obtained 68.8 % including high criteria , the results obtained infrastructure including high criteria 74.6 % , 61.0 % of funds obtained results include lower criteria , and marketing of 70.3 % obtained results including high criteria . The conclusions in this study are the sights properly implement management processes .